2019
DOI: 10.1128/mbio.02994-19
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Protection against Multidrug-Resistant Klebsiella pneumoniae in a Nonhuman Primate Model of Severe Lower Respiratory Tract Infection

Abstract: Klebsiella pneumoniae is a human gut communal organism and notorious opportunistic pathogen. The relative high burden of asymptomatic colonization by K. pneumoniae is often compounded by multidrug resistance—a potential problem for individuals with significant comorbidities or other risk factors for infection. A carbapenem-resistant K. pneumoniae strain classified as multilocus sequence type 258 (ST258) is widespread in the United States and is usually multidrug resistant. Thus, treatment of ST258 infections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Data in humans has shown that neutropenic patients may have reduced survival in cases of bacteremia caused by CR-Kp and other carbapenem-resistant Enterobacteriaceae (23). In mice, some studies have shown neutrophils to be important in CR-Kp clearance (15,27), while others have shown them to be less valuable (25). Using a tube-based incubation assay with human neutrophils, we observed both antibodies to promote neutrophil-dependent killing of MMC39 in the presence of 5% autologous serum at 40 g/ml (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data in humans has shown that neutropenic patients may have reduced survival in cases of bacteremia caused by CR-Kp and other carbapenem-resistant Enterobacteriaceae (23). In mice, some studies have shown neutrophils to be important in CR-Kp clearance (15,27), while others have shown them to be less valuable (25). Using a tube-based incubation assay with human neutrophils, we observed both antibodies to promote neutrophil-dependent killing of MMC39 in the presence of 5% autologous serum at 40 g/ml (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relative contributions of macrophages, monocytes, and neutrophils to CR-Kp clearance has been disputed. While evidence using cell-specific depletions in mice strongly suggested that lung clearance of CR-Kp is predominantly mediated by CCR2positive macrophages over neutrophils (25), studies examining the role of human and primate neutrophils in CR-Kp clearance have shown their efficacy in clearing bacteria in vitro (15,27,47). These contributions matter significantly to the field of anti-infective antibody therapy in the context of CR-Kp, as up to 86% of patients with CR-Kp bacteremia are neutropenic, and these patients have been found to face worse prognoses than patients without neutropenia (19,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, some studies have shown neutrophils to be important in CR-Kp clearance (15,29), while others have shown them to be less valuable (26). Using a tube-based incubation assay with human neutrophils, we observed both antibodies to promote neutrophil-dependent killing of MMC39 in the presence of 5% autologous serum at 40µg/mL ( Figure 3C).…”
Section: Neutrophil Killing Of Cr-kp Improved With Lower Concentratiomentioning
confidence: 87%
“…The relative contributions of macrophages, monocytes, and neutrophils to CR-Kp clearance has been disputed. While evidence using cell-specific depletions in mice strongly suggested that lung clearance of CR-Kp is predominantly mediated by CCR2 positive macrophages over neutrophils (26), studies examining the role of human and primate neutrophils in CR-Kp clearance have shown their efficacy in clearing bacteria in vitro (15,29,49). These contributions matter significantly to the field of anti-infective antibody therapy in the context of CR-Kp, as up to 86% of patients with CR-Kp bacteremia are neutropenic, and these patients have been found to fare worse prognoses than patients without neutropenia (19,28).…”
Section: Discussionmentioning
confidence: 99%